BIOSYNTHESIS, PARTIAL PURIFICATION AND CHARACTERIZATION OF EXTRACELLULAR L-ASPARAGINASE FROM NOVEL BACILLUS SUBTILIS SUBSP. SPIZIZENII TU-B-10 ISOLATED FROM GCU GARDEN SOIL MICROFLORA - FATIMA, H; HUSSAIN, Z; SALEEM, R; SHAIKH, ZA; SIYAL, S; JOKHIO, SA; UNAR, AA; UNAR, K; SHAIKH, SA; SHAIKH, AI; et al. (Biological and Clinical Sciences Research Journal, 2023)
This study focused on L-asparaginase (LA), which breaks down L-asparagine into ammonia and aspartic acid and is known for its anti-carcinogenic properties. A bacterial strain from GCU garden soil was isolated, characterized, and screened for LA production using various assays. Physical and nutritional parameters for maximum LA biosynthesis were optimized by employing one factor at one time (OFAT) optimization strategy. Partial purification of the enzyme was followed by the determination of its various biochemical properties. The phylogenetic analysis has confirmed the close relation of soil isolate SHF-11 to Bacillus subtilis subsp. spizizenii TU-B-10. A twofold increase in enzyme activity with 23.05 IU/ml corresponding to 100 IU/mg of protein was achieved using 2% inoculum size, initial pH 7, agitation at 200 rpm, incubation time, and temperature of 72 hrs and 37 °C, respectively under submerged fermentation consuming 0.1% sucrose as carbon source and 1.5% asparagine as an inducer in the presence of 0.5% tryptone and 0.25% yeast extract as nitrogen source. SDS-PAGE analysis showed that the enzyme exhibited a protein band of almost 40 kDa. The highest activity of LA from Bacillus subtilis subsp. spizizenii TU-B-10 (BsLA) was observed at pH 8 and 37 ºC. EDTA was found to be a strong inhibitor of BsLA activity at the final concentration of 0.1 M, while Mg+2 ions were found to be a strong activator of BsLA. By optimizing purification parameters, more potential and specific preparations of LA are likely to come up that can meet industrial and biomedical standards.